Kesejahteraan masyarakat ASEAN: dimensi beberapa variabel makroekonomi dan kependudukan - Afrianita, Suci; Ridwansyah, M.; Umiyati, Etik (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study aims to analyze the welfare of the people of ASEAN countries as seen from the dimensions of several macroeconomic and population variables and how the development of each variable is in the form of the Human Development Index (HDI), Corruption Perception Index (CPI), unemployment rate, population growth rate and exports- Imports on Economic Growth. The analytical tool used in this study is dynamic panel data with secondary data from 10 countries in Southeast Asia during the period 2015 to 2019. The research approach method used is a quantitative descriptive approach. The results of the study show that the overall development of welfare indicators in ASEAN leads good conditions, except for the condition of level of corruption in ASEAN which is still far from very clean, so this needs to be a common concern of ASEAN countries. Then, the results of dynamic panel regression using the SYS-GMM model as the best model, show that the GDP and Population Growth lag variables have a negative and significant effect on GDP. Furthermore, the HDI, CPI, and Unemployment variables have no significant effect on GDP. Meanwhile, the Export-Import variable has a positive and significant effect on GDP.